A delayed non-autonomous predator-prey model with Crowley-Martin functional response - Tripathi J.P.; Tiwari V. (My University, 2025)
In this work, we propose a delayed non-autonomous prey-predator system with Crowley-Martin functional response (CMFR). Mutual interference by predators at high prey density differentiate between Beddington-DeAngelis functional response and CMFR. We discuss the permanence, extinction, stability, existence and uniqueness of a globally attractive almost periodic solution (APS). In addition to effect of Crowley-Martin parameter, we also show that the intrinsic growth rate leaves positive effect on the permanence of the considered model system. Some numerical examples are also presented to support obtained analytical results. © 2018, Springer Nature Singapore Pte Ltd.